2013
DOI: 10.1177/2050312113517501
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of garlic (Allium sativum) and black seeds (Nigella sativa) in healthy postmenopausal women

Abstract: Objectives:The objective of this study is to investigate the antioxidant effects of garlic extract and crude black seeds’ consumption on blood oxidant/antioxidant levels in healthy postmenopausal women.Methods:In total, 30 healthy postmenopausal women (mean age = 50.31 ± 4.23 years) participated. They ingested two garlic soft gels per day (each is equivalent to 1000 mg of fresh garlic bulb) and crude black seed grounded to powder in a dose of 3 g/day for 8 weeks. Oxidant (malondialdehyde) activity in plasma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 68 publications
2
23
0
1
Order By: Relevance
“…In addition, a placebo controlled participant blinded clinical trial of 114 type 2 diabetic patients consisting equal number of participants in control group and N. sativa group, determined that the patients who received 2gm of N. sativa daily for 1 year have shown enhanced antioxidant defense system through significant elevation in total antioxidant capacity (TAC), superoxide dismutase (SOD), and glutathione levels [ 31 ]. Significant reduction of plasma levels of malondialdehyde (MDA) and increased activity of erythrocyte glutathione peroxidase (GSH-Px) and superoxide dismutase were reported in thirty postmenopausal women who took N. sativa seed and Allium sativum concomitantly for 2 months [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a placebo controlled participant blinded clinical trial of 114 type 2 diabetic patients consisting equal number of participants in control group and N. sativa group, determined that the patients who received 2gm of N. sativa daily for 1 year have shown enhanced antioxidant defense system through significant elevation in total antioxidant capacity (TAC), superoxide dismutase (SOD), and glutathione levels [ 31 ]. Significant reduction of plasma levels of malondialdehyde (MDA) and increased activity of erythrocyte glutathione peroxidase (GSH-Px) and superoxide dismutase were reported in thirty postmenopausal women who took N. sativa seed and Allium sativum concomitantly for 2 months [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…in 2013 assessed the antioxidative effect of Nigella sativa and garlic. 18 They administered 3g/day of Nigella sativa along with garlic to 30 healthy postmenopausal females for 8 weeks and measured the plasma levels of MDA, superoxide dismutase and glutathione peroxidase before and after supplementation. Their results showed that consumption of 3 g /day of Nigella sativa along with garlic reduced MDA levels significantly (P<0.05) and increased the levels of superoxide dismutase and glutathione peroxidase significantly (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This result conform the result of [37] who observed that phytochemical from plant-rich diets, including garlic, provide important additional protection against oxidant damage. Garlic extract supplementation improves blood lipid profile, strengthens blood antioxidant potential, and also leads to a decrease in the level of oxidation product (MDA) in the blood samples, which demonstrates reduced oxidation reactions in the body [38,39]. [40] found that SOD activities were decreased with aging.…”
Section: Discussionmentioning
confidence: 99%